Intergovernmental transfers in federations - Yılmaz, Serdar; Zahir, Farah (Edward Elgar Publishing Limited, 2020)
Contents: Foreword by Richard Bird xiii 1 Introduction to the volume 1 Serdar Yilmaz and Farah Zahir PART I CONCEPTUAL ISSUES 2 The architecture of intergovernmental transfers: principles and practice in low- and middle-income countries 7 Roy W. Bahl Jr 3 Issues in intergovernmental fiscal transfers: public finance and political economy considerations 21 Serdar Yilmaz and Farah Zahir 4 The practice of fiscal equalization: a political economy clarification 41 Bernard Dafflon and François Vaillancourt PART II INTERGOVERNMENTAL TRANSFERS IN MATURE FEDERATIONS 5 The German model of addressing vertical and horizontal fiscal imbalances 64 Paul B. Spahn 6 The United States grant system 86 Howard A.
Titel und Verantwortlichkeitsangabe der Landingpage (Elgaronline) entnommen, da kein Titelblatt vorhanden
Keywords: BUSINESS & ECONOMICS; Public Finance; Public finance; BUSINESS & ECONOMICS; Development; Economic Development; POLITICAL SCIENCE; American Government; Local; Development economics